2020
DOI: 10.3390/ijerph17124420
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Quality Perceptions and Health: A Cross-Sectional Study of Citizens of Kaunas, Lithuania

Abstract: The perception of urban environmental quality is an important contributor when identifying local problems in sustainable development and environmental planning policy. This study examined the associations between environmental and social residential characteristics, physical activity, obesity, and hypertension in Kaunas city, Lithuania. This cross-sectional study analyzed 580 citizens’ demographic-, socioeconomic-, health-, and lifestyle-related factors, environmental health concerns, and environmental quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…A detailed description of the methods of the participants’ enrolment as well as the description of the study have been provided previously [ 11 , 48 ]. The participants together with the scientists were involved in identifying the relevant questions, contributed to data collection, identified environmental problems in the district and health concerns, and participated in the discussion on the study questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the methods of the participants’ enrolment as well as the description of the study have been provided previously [ 11 , 48 ]. The participants together with the scientists were involved in identifying the relevant questions, contributed to data collection, identified environmental problems in the district and health concerns, and participated in the discussion on the study questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…The major health concerns mentioned by the participants were hypertension, obesity, and cardiac problems. A detailed description of the methods of the participants’ involvement, as well as the description of the study, have been provided previously [ 23 ]. All participants gave their informed consent for inclusion before entering the study.…”
Section: Methodsmentioning
confidence: 99%
“…The present study is part of the Horizon 2020 proposal Citizen Science for Urban Environment and Health (CitieS-Health) [ 22 ]. Our previously publicized findings showed that the poor quality of the neighborhood and the individual-level characteristics were those very factors that influenced a higher prevalence of health problems at the district level [ 23 ]. This study had three aims: (1) to estimate whether the citizens’ concerns, neighborhood quality rating and the greenspace usage depended on the education level; (2) to assess the relationships between joint individual SES markers (education and income) and the risk of hypertension; and (3) to test the hypothesis that the differences in the effect of the social environment on hypertension were mediated by exposure to urban green spaces.…”
Section: Introductionmentioning
confidence: 99%
“…In this environmental epidemiological study, we for the first time, investigated the impact of participation on the knowledge of the links between environmental quality and health among 18-75-year-old citizens of an Eastern European country. The study was initiated as the Kaunas pilot study [24,25]. In this environmental epidemiological study, the researchers, together with the engaged citizens, outlined the participants' environmental concerns and major health problems and placed them at the centre of the participatory research to study how the urban design affects citizens' health and well-being and how it might impact physical activity.…”
Section: Introductionmentioning
confidence: 99%